The Hormesis effect of cadmium on Panax notoginseng and corresponding impact on the rhizosphere microorganism - Mingpeng Liu; Xuanxiang Du; Mulan Wang; Yuewen Huo; Yanbo Zeng; Jingheng Wu; Xin Ying; Fugang Wei; Li Liu; Jianguo Tang (Ecotoxicology and Environmental Safety)
Panax notoginseng is a famous Chinese traditional medicinal. However, soil cadmium pollution seriously affected the yield and quality of notoginseng. This study systematically investigated the effects of soil Cd stress at different concentrations on the growth of one-year-old notoginseng. The results indicate that Cd exhibits a typical low-dose stimulation and high-dose inhibition effect on the development of notoginseng. At low concentrations (1 mg/kg), Cd promotes the growth of plants, including increased biomass (∼40 % of root dry weight) and higher saponin contents (∼30 % of total saponins). At high concentrations, Cd inhibits the overall growth and metabolism of notoginseng. Meanwhile, the impact of Cd on the rhizospheric micro-environment shows dose dependency. In a low Cd stress environment, the total and unique microbial populations increase, including Rhizobiaceae, Streptomycetaceae, and Mesorhizobium. Conversely, under strong Cd stress, the richness and diversity of the rhizospheric microbial community decrease, while the abundance of cadmium-tolerant species increases, such as Deinococcus and Rhodanobacter.